Last updated at Feb. 19, 2019 by Teachoo

Transcript

Example 4 Find the sum of (– 9) + (+ 4) + (– 6) + (+ 3) (−9) + (+4) + (−6) + (+ 3) = − 9 + 4 − 6 + 3 = − 9 − 6 + (4 + 3) = − 9 − 6 + 7 Taking − common from −9 & −6 = − (9 + 6) + 7 = − 15 + 7 Taking − common = − (15 − 7) = − 8 Rules + & − becomes + + & + becomes + − & − becomes − Rough We group positive integers together and negative integers together

About the Author

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 10 years. He provides courses for Maths and Science at Teachoo.